2017
DOI: 10.4103/jpp.jpp_109_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Fentanyl and Clonidine to Local Anesthetic Solution in Peribulbar Block

Abstract: Objective:To compare the effect of addition of fentanyl and clonidine as adjuvants to bupivacaine and lignocaine in peribulbar block.Methods:The study was conducted on 105 adult patients of either sex, of ASA grade I and II undergoing ophthalmic surgeries. Patients were randomly divided into 3 groups of 35 each. All the patients were given peribulbuar block with 5ml lignocaine 2% +3 ml bupivacaine 0.5% +1 ml hyaluronidase (250 IU). In addition to this 1 ml normal saline was added to Group S, 25 μg fentanyl to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Our results reported the evidence that addition of fentanyl to anesthesia mixture provide more rapid onset and duration of anesthesia & rapid onset of eyelid akinesia and duration for both lid and global akinesia & less pain perception and less need for analgesia. Poonam Nehra et al [17] compared the addition of fentanyl versus clonidine (selective alpha 2 agonist) to local anesthetic mixture in peribulbar block and reported that the onset time of globe akinesia was significantly shorter in fentanyl group (F) and clonidine group (C) compared to control group (S). They also documented that the durations of motor block and analgesia were significantly longer in Group F and group C compared to group S. The results of the present study are in accordance Open Journal of Anesthesiology with study done by Toshiharu et al [18] who studied the effect of supplementation of fentanyl to mepivacaine in epidural block and found that addition of fentanyl to mepivacaine accelerate the onset of analgesia and enhances the analgesic effect of epidural block.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reported the evidence that addition of fentanyl to anesthesia mixture provide more rapid onset and duration of anesthesia & rapid onset of eyelid akinesia and duration for both lid and global akinesia & less pain perception and less need for analgesia. Poonam Nehra et al [17] compared the addition of fentanyl versus clonidine (selective alpha 2 agonist) to local anesthetic mixture in peribulbar block and reported that the onset time of globe akinesia was significantly shorter in fentanyl group (F) and clonidine group (C) compared to control group (S). They also documented that the durations of motor block and analgesia were significantly longer in Group F and group C compared to group S. The results of the present study are in accordance Open Journal of Anesthesiology with study done by Toshiharu et al [18] who studied the effect of supplementation of fentanyl to mepivacaine in epidural block and found that addition of fentanyl to mepivacaine accelerate the onset of analgesia and enhances the analgesic effect of epidural block.…”
Section: Discussionmentioning
confidence: 99%
“…Poonam Nehra et al [19] compared the addition of fentanyl vs. clonidine (alpha 2 agonist) to local anaesthetic mixture during peribulbar block and reported that the onset time of globe akinesia was significantly shorter in fentanyl group (F) and clonidine group (C) compared to control group (S). They also reported that the durations of motor block and analgesia were significantly longer in Group F and group C compared to group S. On the other hand Hala et al [4] , reported that adding clonidine to local anesthetics for peribulbar block was associated with insignificant difference regarding onset time for sensory and motor block (which disagreed with our result) and improvement in the duration and the quality of the block (which agree with our results).…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl has been added to local anesthetics used for regional anesthesia to improve analgesia (19)(20)(21)(22)(23)(24) . This practice has been taken to reduce complications of systemic opioids, for example cardiorespiratory depression, drowsiness, and postoperative nausea and vomiting (11,(25)(26)(27) .…”
Section: Introductionmentioning
confidence: 99%